Gastric emptying of non digestible solid radiopaque markers and autonomic neuropathy in chronic liver disease - A. Kemal GÜRBÜZ; Levent DEMİRTÜRK; Selahattin HÜLAGÜ; E. KIZILKAYA; S. GÜL; E. KOÇER; M. DANACI; Z. ÇANKIR (Turkish Journal of Gastroenterology, 2020)
-